The Effects of the Recovery Act Upon Labor Organization - McCabe, David A. (Quarterly Journal of Economics, 1934)
The new features of general application introduced by the Act: prohibition of discrimination, 53; right to select a labor organization as the representative with whom employer must deal, 55; fixing of code terms without antecedent collective bargaining, 67; union representation on boards to settle labor disputes in the industry or on code authorities not general, 59. — Effects: strengthening of unions which had already established effective collective action over competitive areas, 62; obstacles to effective collective bargaining over competitive areas within the industry by separate organizations of the unskilled and semi-skilled, 66; importance of feasibility of fixing standard wage rates for better-paid workers over competitive areas, 69; craft vs. vertical unionism in mass-production industries, 71; competition of employee representation plans with outside organizations, 73; stimulus to political action, 77.